EVALUASI PROSES PEMBELAJARAN SENI BUDAYA MENGGUNAKAN METODE DISKUSI DI SDN 1 PERUMNAS WAY KANDIS - Indika, Indika; Saputri, Amelia Hani; Wendhaningsih, Susi (Jurnal Seni dan Pembelajaran, 2023)
This research aims to describe the Evaluation of the Arts and Culture Learning Process Using the Discussion Method at SDN 1 Perumnas Way Kandis. The stages in carrying out an evaluation of the learning process using the discussion method are the planning, implementation and results stages. The method used in this research is qualitative with data collection techniques, namely observation, interviews and documentation. The data analysis techniques used include the data collection stage, data reduction stage, data presentation stage, and drawing conclusions. The research results show that there are three stages in evaluating the arts and culture learning process using the discussion method at SDN 1 Perumnas Way Kandis. Starting from the planning stage by preparing a Learning Implementation Plan and preparing student assessment instruments. In the implementation stage, the teacher creates a conducive learning atmosphere by asking questions about the material that has been studied, providing direction for the discussion by forming students into four groups and providing the main material. In the results stage, the teacher gives a score to the learning process by looking at affective, cognitive and psychomotor aspects. Student scores on the affective, cognitive and psychomotor aspects of the evaluation of the learning process using the discussion method are used as added value in arts and culture learning.